Book review: Facing Forward: Residential Child Care in the 21st Century. David Crimmens and Ian Milligan, editors. - Adrian Ward (Scottish Journal of Residential Child Care, 2006)
This is an extremely useful and timely collection of writing about the state of residential care in the UK. Although it acknowledges the recurrent troubles of this sector and faces quite starkly some of the lessons which have to be learned, the whole book has a constructive and forward-looking tone.